2015
DOI: 10.1021/pr501305g
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Four Biofluids from Dairy Cows: Potential Biomarkers for Milk Production and Quality

Abstract: The fundamental understanding of the mechanisms regulating milk protein synthesis is limited. This study aimed to elucidate the metabolic mechanisms of milk production affected by forage quality through studying metabolites from four biofluids (rumen fluid, milk, serum, and urine) collected from 16 lactating cows fed alfalfa hay (AH, high-quality, n = 8) and corn stover (CS, low-quality, n = 8) using gas chromatography-time-of-flight/mass spectrometry. The cows fed AH exhibited higher milk yield (P < 0.01), mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(167 citation statements)
references
References 46 publications
11
151
1
4
Order By: Relevance
“…In terms of dairy cows, results from both our group and others have confirmed the alterations on the transcriptome level (Ji et al, 2012, Osorio et al, 2014a, Li et al, 2016 as well as metabolome (Sun et al, 2015) level in response to nutritional interventions. For instance, microarray analysis from our group revealed a greater overall subclinical inflammatory-like condition in feed-restricted cows compared with overfed cows (Shahzad et al, 2014).…”
Section: Uncover Adaptations During the Transition Period With Omics supporting
confidence: 83%
See 1 more Smart Citation
“…In terms of dairy cows, results from both our group and others have confirmed the alterations on the transcriptome level (Ji et al, 2012, Osorio et al, 2014a, Li et al, 2016 as well as metabolome (Sun et al, 2015) level in response to nutritional interventions. For instance, microarray analysis from our group revealed a greater overall subclinical inflammatory-like condition in feed-restricted cows compared with overfed cows (Shahzad et al, 2014).…”
Section: Uncover Adaptations During the Transition Period With Omics supporting
confidence: 83%
“…Metabolomics profiling of rumen fluid, milk, serum, and urine from lactating cows fed high-vs. low-quality diets suggest higher N loss and low N utilization efficiency in response to low quality diet (Sun et al, 2015).…”
Section: Uncover Adaptations During the Transition Period With Omics mentioning
confidence: 99%
“…GC-TOF-MS is a widely used approach in metabolomics for its high resolution and sensitivity1328. Metabolomic studies evaluating the effects of Lactobacilli on the intestines of the host are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen multiparous (3.6 ± 1.8 parity) Holstein cows were randomly assigned to 2 groups according to BW and milk yield as described by Sun et al [6]. Both groups were offered consisting of 55 % concentrate mixture and 15 % corn silage with different forages (Additional file 1: Table S1): (1) alfalfa (AH), containing 23 % alfalfa hay and 7 % Chinese wild rye hay, and (2) corn stover (CS), containing 30 % corn stover instead of alfalfa hay and Chinese wild rye hay.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, we characterized certain results for common metabolites in four biofluids (rumen fluid, milk, serum, and urine) [6]. We concluded that a deep analysis of metabolites from a single representative biofluid should be used to generate specific biomarkers and pathways to distinguish the metabolic profiles of dairy cows fed different diets.…”
Section: Introductionmentioning
confidence: 93%